Pemodelan Umur Harapan Hidup di Provinsi NTB dengan menggunakan SEM-PLS - Baskara, Zulhan Widya; Putri, Dina Eka; Purnamasari, Nur Asmita; Zulhan Widya Baskara (FKIP Universitas Mataram, 2024)
Life expectancy (LE) is an essential indicator reflecting public health status and the success of health systems. In Nusa Tenggara Barat (NTB) Province, LE remains below the national average, with significant regional disparities. This study seeks to examine the connections between access to sanitation and clean water, child health, and maternal health in relation to LE in NTB. The research employs the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, which facilitates the analysis of complex interrelationships among variables.The results indicate that sanitation and clean water access significantly influence LE, followed by child health. However, women's and maternal health does not have a significant influence on the improvement of life expectancy in NTB.